Emerging Roles of Long Noncoding RNAs in Immuno-Oncology - Xin Wang (Frontiers Media S.A., 2021)
Long noncoding RNAs (lncRNAs), defined as ncRNAs no longer than 200 nucleotides, play an important role in cancer development. Accumulating research on lncRNAs offers a compelling new aspect of genome modulation, in which they are involved in chromatin remodeling, transcriptional and post-transcriptional regulation, and cross-talk with other nucleic acids. Increasing evidence suggests that lncRNAs reshape the tumor microenvironment (TME), which accounts for tumor development and progression. At the same time, the insightful findings on lncRNAs in immune recognition and evasion in tumor-infiltrating immune cells raise concerns with regard to immuno-oncology. In this review, we describe the essential characteristics of lncRNAs, elucidate functions of immune components engaged in tumor surveillance, and present some instructive examples in this new area.